IDENTIFIKASI PERUBAHAN POLA CURAH HUJAN DAN PERIODE MASA TANAM DI LAHAN KERING UNTUK ADAPTASI PERUBAHAN IKLIM (STUDI KASUS KABUPATEN BONE, SULAWESI SELATAN) - yeli sarvina (Pusbindiklat - LIPI, 2019)
Identification of climate change impacts on spatial and temporal rainfall pattern and length of growing period are very important for climate change adaptation strategy. Rainfed is an agro-ecosystem most sensitive to changes in rainfall patterns. Bone Regency is a center of agriculture in South Sulawesi and has considerable rainfed potentials. This study aims to identify changes of rainfall patterns and length of growing period (LGP) for paddy and upland rice in Bone Regency. Data of three rain stations with a 55-year period were used and Oldeman methods was applied to determine rainfall pattern and LGP. Data was separated in two period, period 1 (1961-1990) and period II (1991-2016). The pattern of changes were identified by comparing rainfall patterns in LGP I and II. This analysis was grouped by wet year, normal year and dry year with criteria developed by BMKG. The results of the analysis showed that the rainfall pattern and LGP had changed of which pattern of change varies between regions. The LGP of paddy in Macope were three months shorter in all years, while for upland rice were two months shorter in wet year, and 1 month in normal year. In Katumpi, the LGP of paddy fields were 2 months shorter comparing to the wet year and 1 month shorter in normal and dry year for upland rice. LGP for paddy in Cellu was lengthened 1 month in wet year and shortened 2 months in dry year for upland rice.